2008
DOI: 10.1093/annonc/mdn351
|View full text |Cite
|
Sign up to set email alerts
|

Pancreatic neuroendocrine tumors (PNETs): incidence, prognosis and recent trend toward improved survival

Abstract: PNETs are uncommon neoplasms but the incidence may be increasing. Age, grade, stage, and functional status predict survival in patients with PNETs. Survival has improved over time, but this is not explained by earlier diagnosis or stage migration.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

13
521
5
19

Year Published

2012
2012
2017
2017

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 760 publications
(558 citation statements)
references
References 23 publications
13
521
5
19
Order By: Relevance
“…It was a nonfunctioning tumour of size 12x7x3 cm which had metastasized to the ovary. In a study conducted by Halfdanarson et al [15] mean age of patients with pancreatic NETs was 58.8 years and 60.2% had metastasized. These findings are in agreement with the present study.…”
Section: Discussionmentioning
confidence: 95%
“…It was a nonfunctioning tumour of size 12x7x3 cm which had metastasized to the ovary. In a study conducted by Halfdanarson et al [15] mean age of patients with pancreatic NETs was 58.8 years and 60.2% had metastasized. These findings are in agreement with the present study.…”
Section: Discussionmentioning
confidence: 95%
“…13 Many small NF-PNETs are discovered incidentally on cross-sectional imaging (CT/MRI) which is being performed more frequently nowadays. 2,14 Recently, the H. Lee Moffitt Cancer Center concluded that 40% of PNETs were discovered incidentally and 55% of tumors were in stage I according to American Joint Committee on Cancer (AJCC) classification. 15 The WHO classification of PNETs was updated in 2010.…”
Section: Discussionmentioning
confidence: 99%
“…Compared with PDA, however, the prognosis is usually much better, with approximately 40 % of affected patients surviving 10 years after diagnosis [126][127][128]. PanNETs are heterogeneous and clinically can be divided into functioning (syndromic) or nonfunctioning (nonsyndromic) tumors.…”
Section: Pancreatic Neuroendocrine Tumorsmentioning
confidence: 99%